ANALISIS VARIABEL YANG MEMPENGARUHI EARNING PER SHARE STUDI EMPIRIS PADA PERUSAHAAN DASAR DAN KIMIA YANG TERDAFTAR DI BEI TAHUN 2016-2017 - Amaraesty, Tashya; Triyanto, Dedik Nur (Aksara Public, 2018)
This study aims to see and know the variables that affect earnings per share in basic and chemical companies listed on the Stock Exchange in the period 2016-2017. By using variable X1 (return on assets), variable X2 (net sales), variable X3 (inventory turnover), variable X4 (net profit margin), variable X5 (current ratio), variable X6 (debt to equity ratio). While the variable Y (earnings per share). The population in this study are all basic and chemical companies listed on the IDX. The sample selection technique taken was purposive sampling and obtained 57 companies with a research period in 2016-2017. Data analysis method is panel data regression analysis using software eviews 9.5. The results of the study show that simultaneously the return on assets, net sales, inventory turnover, net profit margin, current ratio, and debt to equity ratio have a significant effect on earnings per share. Partially the net sales variable, inventory turnover, current ratio and debt to equity ratio do not have a significant effect on earnings per share. While the variable return on assets, net profit margin has a significant effect on earnings per share.